Influence of developmental nicotine exposure on the ventilatory and metabolic response to hyperthermia - Ferng, Jonathan (J Physiol, 2015)
KEY POINTS: Both developmental nicotine exposure and hyperthermia are associated with breathing abnormalities in neonates. Whether or not gestational nicotine exposure interacts with heat stress to alter the normal ventilatory response to hyperthermia is unclear. With moderate thermal stress, nicotine‐exposed rat pups breathed less and had longer apnoeas than control pups, although this was true at both normal and high temperatures, suggesting an effect of gestational nicotine exposure that is independent of body temperature. With severe thermal stress, nicotine‐exposed pups failed to increase pulmonary ventilation, and had a delayed recovery from hyperthermia‐induced gasping. The results show that gestational nicotine exposure has subtle but physiologically significant effects on the ventilatory response to severe hyperthermia, which could impact upon both gas exchange and temperature regulation in infants with fever, excessive swaddling or exposure to hot environmental temperatures. ABSTRACT: To determine whether developmental nicotine exposure (DNE) alters the ventilatory and metabolic response to hyperthermia in neonatal rats (postnatal age 2–4 days), pregnant dams were exposed to nicotine (6 mg kg(−1) of nicotine tartrate daily) or saline with an osmotic mini‐pump implanted subdermally on day 5 of gestation. Rat pups (a total of 72 controls and 72 DNE pups) were studied under thermoneutral conditions (chamber temperature 33°C) and during moderate thermal stress (37.5°C). In all pups, core temperature was similar to chamber temperature, with no treatment effects. The rates of pulmonary ventilation ([Formula: see text]), O(2) consumption ([Formula: see text]) and CO(2) production ([Formula: see text]) did not change with hyperthermia in either control or DNE pups. However, [Formula: see text] was lower in DNE pups at both chamber temperatures, whereas the duration of spontaneous apnoeas was longer in DNE pups than in controls at 33°C. The [Formula: see text] / [Formula: see text] ratio increased at 37.5°C in control pups, although it did not change in DNE pups. To simulate severe thermal stress, additional pups were studied at 33°C and 43°C. [Formula: see text] increased with heating in control pups but not in DNE pups. As heat stress continued, gasping was evoked in both groups, with no effect of DNE on the gasping pattern. Over a 20 min recovery period at 33°C, [Formula: see text] returned to baseline in control pups but remained depressed in DNE pups. In addition to altering baseline [Formula: see text] and apnoea duration, DNE is associated with subtle but significant alterations in the ventilatory response to hyperthermia in neonatal rats.